Pravni vidik družinske ustave - Primec, Andreja (Podjetje in delo, 2021)
Family constitutions began to emerge as a form of autonomous regulation of relationships in family businesses, emphasising family-to-company interaction. Unlike public companies, whose business and governance are subject to more specific legal principles, the principle of parties' freedom prevails for non-public companies. This legal privilege is a significant burden on family businesses, so they must seek the help of legal professionals. A specific version of governance, called family governance, began forming from the otherwise better-known and established corporate governance. Family governance codes with guidelines for responsible control of family businesses begin to emerge. In addition to the governance guidelines for family businesses, the German Governance Code for Family Businesses explicitly points out that each family business is specific, so it must primarily introduce its governance policy and adopt its own (family) code of governance. It also requires that the family code determines its legal nature and content, particularly for relationships to the company's founding and other legal acts. The family constitution can also represent the family code.
Keywords: družbena pogodba; družinska ustava; družinsko upravljanje; family constitution; family governance; family law; freedom of contract; moral duty; moralna obveznost; pogodbena svoboda; shareholder agreement